The Implementation of Strategic Management: Using Balance Scorecard Method at The Department of Islamic Education of IAIN Kerinci - Zebua, Ali Marzuki; Anwar, Khairul (Institut Agama Islam Negeri Lhokseumawe, 2022)
Abstract: One of the main concerns of religious universities is the modernisation of education in terms of the quality of educational services. The transformation of the educational system with a focus on a competitive and high-quality output market necessitates strategic change management. This study aims to discover, characterize, and evaluate strategic management models in terms of quality. Presently, the Balanced Scorecard is considered to be an efficient quality measurement concept. This qualitative study employed comparative and interactive models design with both financial and non-monetary factors are being examined. The results demonstrated that the effectiveness of the Islamic Education program was preferable than that of its competitors (program). Furthermore, the Islamic Education Program is better compared to other undergraduate study programs in both financial and non-financial management. Abstrak: Salah satu problematika perguruan tinggi keagamaan adalah respon terhadap modernisasi pendidikan pada sektor mutu layanan pendidikan. Untuk itu diperlukan manajemen strategi terhadap perubahan adalah transformasi sistem pendidikan dengan orientasi pasar output yang kompetitif dan berkualitas. Penelitian ini bertujuan untuk menganalisis, mendeskripsikan dan menemukan model manajemen strategi dalam perspektif mutu. Saat ini metode Balanced Scorecard dinilai sebagai model pengukuran mutu yang efektif. Penelitian berjenis kualitatif metode studi kasus dengan model komparatif dan interaktif. Analisis dilakukan terhadap aspek keuangan dan non keuangan. Hasil penelitian menunjukkan efektivitas pelaksanaan program prodi PAI berada pada posisi agresif (maju) dalam menghadapi para kompetitornya. Prodi PAI juga lebih baik dari aspek pengelolaan keuangan dan non-keuangan dibandingkan prodi lain di lingkungan IAIN Kerinci.